OPTIMASI BIAYA PENGIRIMAN KELAPA MENGGUNAKAN MODEL TRANSPORTASI METODE STEPPING STONE - Muhamad Anwar Septiana; Rifki Hidayattulloh; Jamari Machmudin; Nitta Fitria Anggraeni (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
Coconut is one of the commodities that is quite important for food needs in Indonesia, especially for dishes made from coconut milk and grated coconut. This study aims to resolve the problem of coconut shipping costs at the level of coconut wholesalers with the name of the owner Mr. Yayan in the Greater Bandung area. Coconut is supplied from 3 regions namely Tasikmalaya, Lampung and Riau. Of the three regions, coconuts will be stored in 3 warehouses, namely Karapitan, Ciganitri and Cikoneng. From the three warehouses, coconut will be distributed to 3 markets in Bandung, namely Cijerah Market, Batu Buah Market and Baleendah Market. Coconut shipping uses land transportation such as pick up cars. Shipping costs are calculated based on the amount per coconut to be sent to the market. To optimize shipping costs to 3 markets in Bandung, the Northwest Corner (NWC) transportation model is used. The initial step to completing the optimal shipping transportation costs is by establishing shipping costs from the warehouse to the market, the amount of coconuts stored in the warehouse and the demand for coconuts in each market into the transportation model. The direct calculation of the cost of transporting coconut shipments from 3 warehouses to 3 markets using the Northwest Corner model is Rp 167,500. Furthermore, looking for the most optimal results using the Stepping Stone method that can provide an optimal solution to the cost of transporting coconut shipping to Rp 147,500 So by finding the most optimal results using the Stepping Stone method can save transportation costs of shipping coconut from the warehouse to the market by Rp 20,000.